A boron-decorated melon-based carbon nitride as a metal-free photocatalyst for N2 fixation: a DFT study. Issue 38 (23rd September 2020) - Zheng, Mei; Li, Yi; Ding, Kaining; Zhang, Yongfan; Chen, Wenkai; Lin, Wei
Abstract : The boron-decorated melon-based carbon nitride is a promising metal-free photocatalyst for N2 reduction to NH3 with outstanding selectivity and efficiency. Abstract : On the basis of the electron "acceptance-donation" concept, a boron decorated melon-based carbon nitride (CN) is studied as a metal-free photocatalyst to efficiently reduce N2 to NH3 under visible light irradiation. The results revealed that a boron-interstitial (Bint )-decorated melon-based CN has an outstanding N2 reduction capacity through the enzymatic mechanism with a rather low overpotential (0.32 V). The excellent efficiency and selectivity of Bint -decorated melon-based CN in N2 reduction reaction (NRR) are attributed to the concentrated spin polarization on the B atom, the significant enhancement of visible and infrared light absorption, and the effective inhibition of the competitive hydrogen evolution reaction (HER). Importantly, B-doped melon-based CN has been successfully synthesized in the experiments, so obtaining Bint -decorated melon is promising, while proton transfer from the –NH2 group in CN to the B atom surely will affect the functionality of the catalyst through deactivation of the N2 adsorption site. Our study provides a novel single atom metal-free photocatalyst with high efficiency for NRR, which is conducive to the sustainable synthesis of ammonia.